Time-integrated 3D approach of late Quaternary sediment-depocenter migration in the Tagus depositional system: From river valley to abyssal plain - Vis, Geert-jan; Kasse, Cornelis; Kroon, Dick; Vandenberghe, Jef; Jung, Simon; Lebreiro, Susana M.; Rodrigues, Teresa (Earth-Science Reviews, 2016)
Quantification of sediment volumes in continental to deep ocean basins is key to understanding processes of sediment distribution in source-to-sink depositional systems. Using our own and published data we present the first quantification of sediment-volume changes in basins along the course of a major southwest European river during the deglaciation. The salient points of this quantitative record in the Tagus and equivalent North Atlantic basins show crucial roles for sea level, climate and land-use in the distribution of sediments. The bypass of sediments starved the Tagus basins, and subsequently sedimentation mainly occurred on the Tagus Abyssal Plain during the sea-level lowstand of the Last Glacial Maximum. The main sediment depocenter rapidly shifted via the continental shelf to the Lower Tagus Valley during sea-level rise in the deglaciation period. Finally, the main sediment depocenter shifted further landward into the Lower Tagus Valley during sea-level high stand in the Holocene. During the high-stand phase (last 7 ky), sediment flux increased up to 2.5 times, due to climate and land-use changes. The average catchment denudation rate during the last 12 ky (0.04-0.1 mm/y) is in agreement with those of other European catchments. Our study clearly demonstrates the added value of detailed knowledge of 3D depocenter distribution, size and chronology. This allowed us to identify an increased sediment flux during the last 7 ky, which was not identified using local observations from boreholes alone. The uniqueness of the Tagus depositional system lies in the combination of a large accommodation space in the bedrock-confined Lower Tagus Valley, the steep lowstand-surface gradient and the narrow continental shelf with canyons indenting the shelf break.